2004
DOI: 10.1038/sj.bjc.6601851
|View full text |Cite
|
Sign up to set email alerts
|

CYFRA 21-1 is a prognostic determinant in non-small-cell lung cancer: results of a meta-analysis in 2063 patients

Abstract: The purpose of this study was to determine the prognostic significance of a high pretreatment serum CYFRA 21-1 level (a cytokeratin 19 fragment) adjusted for the effects of well-known co-variables in non-small-cell lung cancer (NSCLC). This meta-analysis based on individual updated data gathered comprehensive databases from published or unpublished controlled studies dealing with the prognostic effect of serum CYFRA 21-1 level at presentation in NSCLC of any stage (nine institutions, 2063 patients). Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
125
1
11

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 55 publications
7
125
1
11
Order By: Relevance
“…In addition to known unfavourable prognostic implication of high pretreatment CYFRA 21-1 in advanced NSCLC (Pujol et al, 2004), we have observed that therapy-induced 2-CYFRA 21-1 impacts survival even more. Inclusion of 2-CYFRA 21-1 and NP in the Cox model replaced pretreatment CYFRA 21-1, PS and stage of disease, becoming the major determinants of survival with relative risks 0.40 and 0.55, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to known unfavourable prognostic implication of high pretreatment CYFRA 21-1 in advanced NSCLC (Pujol et al, 2004), we have observed that therapy-induced 2-CYFRA 21-1 impacts survival even more. Inclusion of 2-CYFRA 21-1 and NP in the Cox model replaced pretreatment CYFRA 21-1, PS and stage of disease, becoming the major determinants of survival with relative risks 0.40 and 0.55, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Using commercial kit, CYFRA 21-1 is easily assessable and its role as prognostic marker alone (Pujol et al, 2004) or in combination (Barlési et al, 2004) has been demonstrated. Furthermore, the prognostic value of CYFRA 21-1 in the present study was higher than that of clinical (performance status, weight loss) or biological (leucocytes, liver enzymes) traditional prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of CYFRA 21-1 for non-small-cell lung cancer (NSCLC) patients was recently definitively demonstrated in a meta-analysis in 2063 patients (Pujol et al, 2004). In the same time, epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKI) as gefitinib emerged as an accepted treatment in second-or third-line setting in NSCLC (Pfister et al, 2004).…”
mentioning
confidence: 99%
“…More extensive studies with clinically relevant models are required to prove the merit of the proposed A high pretreatment CYFRA 21-1 level emerged as an unfavorable prognostic determinant at the 1-year end point, and, remained an unfavorable prognostic determinant at the 2-year end point (together with a locally advanced stage). 9 Au et al 26 submitted a panel of 18 immunomarkers to unsupervised hierarchical clustering analysis to investigate the possibility of identifying different subgroups in a series of 284 patients with nonsmall cell lung cancers. These authors report that the analysis of the three different World Health Organization (WHO) subtypes (namely, adenocarcinomas, squamous cell carcinomas and large cell carcinomas) showed that different markers were significant in different subtypes, but did not behave as significant prognostic predictors in the case of these carcinomas as a group.…”
Section: Discussionmentioning
confidence: 99%
“…4 Modern literature accordingly emphasizes the search for new biological prognostic markers in order to refine the prognostic value contributed by tumor staging and histopathological analyses. [4][5][6][7][8][9] Among the biological markers whose diagnostic and prognostic values have already been demonstrated in various types of cancers are galectins in general, [10][11][12] and galectin-3 in particular. 13,14 In all, 14 galectins have been identified to date 10,11 which function as cell receptors for the N-acetyl-lactosamine (LacNAC) moieties present on most of the extracellular matrix components.…”
mentioning
confidence: 99%